Profile of physical fitness college student during covid-19 pandemic - Muhammad Saleh; Firman Septiadi (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2021)
This study aims to determine the level of physical fitness (VO2Max) of prospective new students during the Covid-19 pandemic. This type of research is descriptive with a quantitative approach. The method used is a survey with data collection techniques using tests and measurements. The sample in this study was the prospective new students 20 male and 8 female, the total sample 28 people. This study uses a total sampling technique. The data analysis technique uses a frequency distribution. Data collection was carried out in the yard of Building D, Muhammadiyah University of Sukabumi. The test instrument used in this study is the Multistage Fitness Test (MFT) or bleep test. The results showed that the majority of prospective new students were in the very poor category with 18 men (90%) and less than 2 (10%), while women who were in the very poor category 7 people (87.5) and category of less than 1 person (12,5%). It can be concluded that the level of physical fitness of prospective new students is in the very poor category.